(3GdefJbi aj GdCMcGes - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s
(3ChdgG (B:s
(3fMh GdbHdI QGaYG jOjg hbdJ ROg aLYdg GdCjef Ydi GdCjSQ s
(3BNQgG (B:s
(3Yf CHj ehSi Cf GdfHi Udi Gddg Ydjg hSde (B( (3aEf GdejJ CfJ fGUQgG hCfJ JMGSHgG(B) (3QhGg CMeO s
(3GdfSNI HgG MhGTs
(3bWYI efg abWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B144s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1851s
(3JHUQGJ GdCUd (B:s
Keywords: (3CUhd Gdabgs